Improving Australia's schools : executive summary of Making schools more effective : report of the Australian Effective Schools Project - Piper, Kevin.; Banks, Diana.; Evans, Beryl.; McGaw, Barry. (Australian Council for Educational Research, 1993)
This is an executive summary of Making Schools More Effective: Report of the Australian Effective Schools Project.